Advanced modeling and experimental validation of an optimized power transformer tank - Mendes, Helder F. G. (2019)
Even though the power transformers are electrical machines, their design includes several important steps with strong emphasis on mechanical engineering topics, such as the design of welded metallic structures. Indeed, the tank and its cover are typically manufactured from steel sheets or plates to which a group of stiffeners are added, with the objective of reducing the bending stress, transverse displacements and/or buckling. The current communication presents and discusses several incremental innovations in the structural design and simulation of tanks for Core type power transformers, including: (i) optimization of the stiffeners design and welding bead volume reduction; (ii) optimization of panels curvature; (iii) simulation of the transformer tank loaded by both hydrostatic pressure and vacuum conditions; and (iv) inclusion of non-linear behavior to more accurately simulate representative structures. Achieved numerical results are compared with obtained experimental data, to evaluate the design procedures and the potential of virtual testing of new solutions.